Healing at Gunung Salak: Festival Budaya untuk Promosi Desa Wisata Gunung Salak Selemadeg Timur Tabanan Bali - Arini, Ni Nyoman; Artha Putra, I Nengah Sandi (Humanis; Vol 27 No 4 (2023)DO - 10.24843/JH.2023.v27.i04.p06, 2023)
Gunung Salak Tourism Village is located in East Selemadeg District, Tabanan Regency, Bali Province which is a tourism village that is still developing, meaning that there still needs to be many breakthroughs in promotion. The spread of Covid-19 has caused Gunung Salak Tourism Village to experience a decrease in tourist visits. After the pandemic, Gunung Salak Tourism Village (Dewi Gula) Festival 2022 was held for the first time as one of the efforts to recover tourism while introducing the tourism potential in Gunung Salak Tourism Village to the wider community. Marketing Mix 8P which includes Product, Price, Place, Promotion, People, Packaging, Programming, and Partnership is used to analyze the Dewi Gula Festival event as a regional tourism promotion media. The results of this study show that the Dewi Gula Festival with the theme "Healing at Gunung Salak" promotes the potential of Gunung Salak Tourism Village in the development of healing tourism and supports sustainable tourism. This can be seen from the implementation of the Dewi Gula Festival which supports the preservation of nature, culture, local identity, environmental awareness, and involves the participation of local communities.